Struggles of the Historian with Film History. Notes on the Margins of Piotr Kurpiewski’s Book, History on the Screen of People’s Poland, Wydawnictwo Uniwersytetu Gdańskiego, Gdańsk 2017, pp. 304 - Witek, Piotr (Sensus Historiae, 2019)
The article consists of two parts. In the introduction, the author briefly discusses how European and American historians Mark Ferro, Robert A. Rosenstone, Hayden White have written about historical cinema. Their research proposals are the starting point for analysis the Polish historian Piotr Kurpiewski’s work: History on the screen of People’s Poland, carried out in the second part of the article. In this part, the author polemically refers to the concept of writing about historical film contained in the Kurpiewski’s monograph. He states that Kurpiewski’s work is a part of the traditional current of research into historical cinema. The book is an example of the political history of film. The issues of historical cinema debated in the book are discussed and presented in chronological order. The narrative is descriptive. Kurpiewski’s book focuses mainly on discussing the content and reception of films in the historical and political context of their creation. The author of the article notes that Kurpiewski in his book discusses historical films from the perspective of their formal construction to a small extent. Kurpiewski’s selection of films for analysis is also disputable. In conclusion of the article the author states that, despite critical comments, Piotr Kurpiewski’s book is an interesting and valuable publication discussing the historical cinema of People’s Poland. The monograph of the Polish researcher inspires discussion and reflection not only on historical cinema, but also on how to think and write about the issue of visualizing history on the screen.